Odpowiedzi

2009-11-23T21:44:28+01:00
A) 3x²+6=3x(x-2)
3x²+6=3x²-6x
3x² się skrócą
-6x=6 / *(-1)
6x=-6/ :6
x=-1

b)x²+3x+2x+6=x²+1x+2 (x² się skrócą)
5x+6=x+2 / -x
4x+6=2 /-6
4x=-4 / 4
x=-1
2009-11-23T21:45:27+01:00
A) 3x²+6=3x(x-2)
3x²+6=6x²-6x
3x²-6x²+6x-6=0
-3x²+6x+6=0 /: (-3)
x²-2x-2=0
Δ=4+8
Δ=12
√Δ=2√3

x₁=2-2√3/2
x₂=2+2√3/2

b) (x+2)(3+x)=x(x+1)+2
3x+x²+6+2x=x²+x+2
3x+x²-x²-x=2-6
2x=-4
x=-2

c) (3a-7)a+5=a²+2a(a-1)
3a²-7a+5=a²+2a²-2a
3a²-7a-3a²+2a=-5
-5x=-5
x=1

d) -(x-3)(2x+1)=-2(6+x²)
-(2x²+x-6x-3)=-12-2x²
-2x²-x+6x+3=12-2x²
-2x²+2x²+5x=12-3
5x=9
x=⁹/₅
2009-11-23T22:10:23+01:00
A) 3x²+6=3x(x-2)
3x²+6=3x²-6
równanie sprzeczne


b) (x+2)(3+x)=x(x+1)+2
3x+x²+6+2x=x²+x+2
4x=-4 /4
x=-1

c) (3a-7)a+5=a²+2a(a-1)
3a²-7a+5=a²+2a²-2a
-5a=-5 /-5
a=1

d) -(x-3)(2x+1)=-2(6+x²)
-(2x²+x-6x-3)= -12-2x²
-2x²-x+6x+3= -12 - 2x²
5x=-15 /5
x=-3